2017
DOI: 10.3945/an.116.013896
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Animal Science Research on Global Maternal and Child Nutrition and Health: A Landscape Review

Abstract: High among the challenges facing mankind as the world population rapidly expands toward 9 billion people by 2050 is the technological development and implementation of sustainable agriculture and food systems to supply abundant and wholesome nutrition. In many low-income societies, women and children are the most vulnerable to food insecurity, and it is unequivocal that quality nutrition during the first 1000 d of life postconception can be transformative in establishing a robust, lifelong developmental trajec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 117 publications
(142 reference statements)
1
21
0
Order By: Relevance
“…In addition, we have indicated a role for DHA in epigenetic regulation, which adds to current knowledge. Using pigs as an agrimedical model ( 15 ), this experiment has laid a foundation for understanding the implications of maternal nutrient restriction and possible nutrition therapy options for supporting fetal growth and development despite nutritional inadequacy. Because swine are a litter-bearing species, there was an advantage in being able to compare LBW to NBW littermates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have indicated a role for DHA in epigenetic regulation, which adds to current knowledge. Using pigs as an agrimedical model ( 15 ), this experiment has laid a foundation for understanding the implications of maternal nutrient restriction and possible nutrition therapy options for supporting fetal growth and development despite nutritional inadequacy. Because swine are a litter-bearing species, there was an advantage in being able to compare LBW to NBW littermates.…”
Section: Discussionmentioning
confidence: 99%
“…Swine are litter bearing ( 14 , 15 ), and so nutrients delivered to the mother are distributed differently to the fetuses depending on their location along the uterine horn. This causes littermates to develop unique physiologic phenotypes, allowing for assessment of differences influenced specifically by nutritional availability, while minimizing differences influenced by genetics.…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, adequate protein intake is recommended to ensure that the additional nitrogen demands of both mother and fetus are met since an increase in protein turnover to meet the requirements for rapid embryo growth occurs at this stage [9]. Based on these findings, the protein restriction model is one of the most well-characterized models of early growth restriction [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Myostatin has been recognized as the only negative regulator of muscle growth and development in animals, since Mcpherron et al (1997) firstly reported the mutagenic effect of Myostatin gene (or MSTN) in cattle. Myostatin has been identified as a negative regulator of skeletal muscle mass and inactivating mutations in the MSTN gene are responsible for the development of a hypermuscular phenotype, because Myostatin(−/−) mutant mice exhibit a generally and significantly increased skeletal muscle mass in which muscle atrophy occurs (Mcpherron et al, 1997;Kawada et al, 2001;Mcfarlane et al, 2006;Chelh et al, 2009), Myostatin is also regarded to play important roles in the maintenance of muscle homeostasis and regeneration (Mcpherron et al, 1997;Kawada et al, 2001;Mcfarlane et al, 2006;Chelh et al, 2009;Odle et al, 2017;Rossi et al, 2016). If Myostatin is knocked out in laboratory animals, the animal mutation would affect both the growth and development of adipose tissues and skeletal muscle tissues.…”
Section: Myostatinmentioning
confidence: 99%
“…Furthermore, the genetic regulation of myogenesis and muscular development and growth of animal muscle tissues is a highly complex and comprehensive successive process, which is affected by many genetic and physiological and environmental influencing factors, such as the genotype and/or haplotype and gender of animal species and/or strains (genetics), endocrine status (physiology), dietary feed level (nutrition), living and feeding environment and other internal and external factors. The effects of genetics and physiology and nutrition and other factors on the growth and development of animal muscle mass are finally implemented through the functional integration of myogenic regulatory factors and their receptors (Odle et al, 2017;Rossi et al, 2016). Fig.…”
Section: Introductionmentioning
confidence: 99%